Comedy and tragedy : latest in contemporary Malaysian politics = komedi dan tragedi : politik mutakhir Malaysia - A. Kadir Jasin (Kuala Lumpur : Berita Publishing, 2009)
'This book attempts to track issues and developments that took place after the 2008 General Election, which contributed towards accelerating the erosion of Abdullah's power and influence, through my writing in my blog'The Scribe A Kadir Jasin''--p. xxviii.
Keywords: Malaysia -- Politics and government -- 21st century